Wave-absorbing honeycomb composite material with absorbent in spatial gradient distribution and preparation method of wave-absorbing honeycomb composite material
By pressing the gradient-distributed wave absorbing film layer into the hole grid of the semi-cured aramid paper honeycomb core material to form an impedance matching structure, the problem of poor absorption performance and difficulty in curved surface molding in the prior art is solved, and a curved wave absorbing honeycomb composite material with excellent absorption performance in the ultra-wide frequency range is realized.
Patent Information
- Application Number
- CN202411693791.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing aramid paper wave absorbing honeycombs have poor absorption performance in the ultra-wide frequency range, and it is difficult for traditional processes to achieve impedance matching structure and curved surface molding.
By pressing the wave absorbing film layer with different electromagnetic characteristics into the hole grid of the semi-cured honeycomb core material, the electromagnetic characteristics change in gradient along the hole grid direction, forming an impedance matching structure. The wave-absorbing honeycomb core material is applied to the curved surface and is adhered to the wave-transmissive skin to obtain excellent wave-absorbing performance.
It realizes a wave-absorbing honeycomb composite material with excellent wave-absorbing performance in the ultra-wide frequency range, and can be formed on the curved surface to meet the stealth needs of curved surface products.
Smart Images

Figure CN119567656A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a wave-absorbing honeycomb composite material with spatial gradient distribution of absorbent and a preparation method thereof, belonging to the technical field of wave-absorbing material preparation. Background Art
[0002] Aramid paper honeycomb is a new type of lightweight structural sandwich material with the advantages of low density, high mechanical properties, and good heat resistance. It is mainly used in lightweight sandwich structures and has been widely used in aircraft. With the development of detection technology, aircraft have been asked to have a wider absorption band and a stronger absorption effect. Aramid paper honeycomb has excellent electromagnetic wave transmission performance, but does not have electromagnetic wave absorption performance, so it cannot be directly used in the field of wave absorption. The conventional idea is to achieve this by introducing electromagnetic wave absorbers on the aramid paper wave-transmitting honeycomb wall.
[0003] At present, most of the existing aramid paper absorbing honeycombs are made by first preparing ordinary aramid paper without electromagnetic loss function into aramid paper transparent honeycombs, then impregnating the honeycomb walls of the aramid paper transparent honeycombs with electromagnetic wave absorbent glue, and finally curing and forming. For example, in patent CN114228266A, by gradient impregnation, the absorbent is gradiently distributed along the honeycomb grid or in the direction perpendicular to the honeycomb grid to obtain an impedance matching structure and better absorbing performance. However, the absorbing honeycomb obtained by the impregnation method has the absorbent attached to the hole wall, which is easy to fall off, and has poor environmental resistance. In addition, the impregnation process is difficult to control and has poor process stability. The impregnation process cannot apply large aspect ratio carbon fiber and magnetic fiber absorbents, resulting in low magnetic loss performance of the aramid paper absorbing honeycomb. In addition, the impregnation process has poor controllability, resulting in low stability of the electromagnetic performance of the aramid paper absorbing honeycomb.
[0004] In order to avoid the shortcomings of impregnated absorbing honeycombs, a method of adding a carbon fiber absorbent to aramid paper to obtain absorbing aramid paper and then preparing an absorbing honeycomb is proposed in a patent for dielectric loss aramid paper, absorbing honeycomb and preparation method (CN112553942A). The advantages of this method are that the absorbent in the aramid paper has good environmental resistance, the amount of absorbent added can be accurately controlled, and the process is stable; however, this method is subject to the mixing papermaking process, and only fiber absorbents can be added, and the amount added should not be too high. It does not have excellent absorbing effect in an ultra-wide frequency range, and generally has a poor low-frequency effect; and using the traditional honeycomb preparation process, the characteristics and tension of different regions of the absorbing aramid paper are different, and it is difficult to ensure the uniformity of the honeycomb grid. Another method is to apply an absorbent on aramid paper to obtain absorbing aramid paper, and then prepare an absorbing honeycomb, such as patents CN109796624A, CN202111440881.5, and CN114214871A; this method can add various types of absorbents, and a large amount of absorbents can be added to meet different absorbing needs; the absorbent is applied to the surface of the aramid paper to obtain absorbing aramid paper, and then the absorbing honeycomb is obtained by the traditional honeycomb preparation method. However, when preparing the absorbing honeycomb by this method, it is necessary to stretch it to form a hexagonal grid. When the absorbent coating has insufficient adhesion, debonding is prone to occur, and the absorbent coating thickness should not be too thick, and the absorbent content is not high. At present, both of the above methods can obtain absorbing honeycombs with stable performance and excellent environmental resistance, but the absorbent content in the honeycomb is fixed and not high, and the absorbing structure design is not performed. The absorbing honeycomb as a whole presents a single electromagnetic characteristic, and there is no impedance matching design, so it is difficult to obtain excellent ultra-wideband absorbing performance.
[0005] In order to obtain an impedance matching structure, the commonly used method is to introduce an absorbing layer between the honeycomb sheet layers, design an absorbing structure, and obtain an absorbing honeycomb composite material with good absorbing performance, such as the paper Design of Type A Skin Composite Honeycomb Structure and Its Absorption Performance (Journal of Composite Materials, 2022, 39(3): 1180-1185). However, in this structure, stress concentration points will be formed at the intersection of the two layers of honeycomb sheets, which are very easy to damage, thereby reducing the compressive strength of the overall structure; and there are many adhesive surfaces between the honeycomb layers, which will also affect the reliability of the overall structure.
[0006] In the patent of an absorbing honeycomb with impedance matching structure and its preparation method (CN115891293A), an absorbent is coated on aramid paper, and an absorbing honeycomb is prepared by a template method, which has an impedance matching structure in the cell direction. By stacking the pattern units, rods are inserted into the honeycomb cells, and pressure is applied to the honeycomb cell walls to ensure the bonding strength of the core strip glue. The preparation method in this patent determines that it is impossible to prepare a curved absorbing honeycomb with a semi-cured absorbing honeycomb core material.
[0007] The absorbing honeycombs mentioned in the above studies are all flat and cannot be used on some curved components (such as air intakes), and the cured honeycombs cannot be bent to change their shape. For homogeneous absorbing honeycombs, the required curved shape can be obtained by machining the surface. However, for impedance matching absorbing structures, the thickness of each layer cannot be changed, cannot be machined, and the outer contour of the curved surface cannot be obtained. Summary of the invention
[0008] The purpose of the present invention is to overcome the differences in the prior art and provide an absorbing honeycomb composite material and a preparation method thereof which has easy process control, excellent absorbing performance and mechanical properties, can be used for curved surface molding, and has a spatial gradient distribution of absorbent, and has excellent absorbing performance in an ultra-wide frequency range.
[0009] The present invention combines the characteristics of multi-layer absorbing honeycombs to propose an absorbing honeycomb composite material and a preparation method that has an impedance matching structure and a spatial gradient distribution of absorbers and can be used for curved surface molding. According to the electrical performance design, absorbing adhesive film layers with different electromagnetic properties are pressed into the cells of the semi-cured honeycomb core material, and the electromagnetic properties change gradiently along the cell direction to obtain an impedance matching structure. The absorbing honeycomb is attached to the surface (curved surface) of the product or mold and cured to obtain a heat-set absorbing honeycomb core material; the upper and lower surfaces are respectively bonded to the wave-transparent skin to obtain an absorbing honeycomb composite material with excellent performance to meet the stealth requirements of curved products.
[0010] The technical solution of the present invention:
[0011] A microwave-absorbing honeycomb composite material with a gradient distribution of absorbent comprises an upper skin, a lower skin, a honeycomb core material and a microwave-absorbing adhesive film layer; the honeycomb core material is formed by curing a semi-cured honeycomb core material; the microwave-absorbing adhesive film layer is located in the cells of the honeycomb core material, and the honeycomb core material containing the microwave-absorbing adhesive film layer is located between the upper skin and the lower skin; the microwave-absorbing adhesive film layer contains an absorbent, and the electromagnetic properties of the absorbent in each microwave-absorbing adhesive film layer are distributed in a gradient.
[0012] Furthermore, the absorbing honeycomb composite material is designed according to electrical properties, and absorbing adhesive film layers with different electromagnetic properties are pressed into different positions in the cells of the semi-cured honeycomb core material, and the electromagnetic properties change gradually along the cell direction to obtain an impedance matching structure. The semi-cured honeycomb core material containing the absorbing adhesive film layer is attached to the surface (curved surface) of the product or mold for curing to obtain a heat-set absorbing honeycomb core material; the upper and lower surfaces of the absorbing honeycomb core material are respectively bonded to the transparent skin to obtain excellent absorbing performance and meet the stealth requirements of curved products.
[0013] Furthermore, the semi-cured honeycomb core material is aramid paper impregnated with phenolic resin, which is dried to remove the solvent; and then subjected to low-temperature and long-term treatment to adjust the phenolic resin to a semi-cured state, thereby ensuring that the honeycomb core material has a certain compressive resistance and retaining the heat setting ability of the honeycomb core material.
[0014] Furthermore, the low-temperature and long-term treatment has a treatment temperature of 70° C. to 90° C. and a treatment time of 6 h to 12 h. During the low-temperature treatment, it is also necessary to ensure that the phenolic resin on the honeycomb pore walls does not flow along the pore walls.
[0015] Furthermore, the wave-absorbing adhesive film layer is composed of an absorbent and an adhesive, and has a thickness of 0.5 mm to 3 mm.
[0016] Furthermore, the absorbent has electromagnetic loss capability and is one or more of carbonyl iron powder, iron silicon aluminum, iron cobalt nickel, ferrite, etc., with a content of 30wt% to 85wt%.
[0017] Furthermore, the adhesive is one of epoxy resin, phenolic resin and bismaleimide resin, preferably phenolic resin.
[0018] Furthermore, electrical performance design is carried out to determine the type of absorbent; electromagnetic simulation software is used to calculate and optimize the best gradient absorbing structure, and the number of absorbing film layers in the absorbing honeycomb, the position of the absorbing film layers in the honeycomb cells, the thickness of each absorbing film layer and the content of the absorbent are determined.
[0019] Furthermore, the upper skin and the lower skin are wave-transmitting resin-based composite materials, including a reinforcement layer and a matrix, wherein the reinforcement layer is one of wave-transmitting fiber cloths such as quartz fiber cloth and glass fiber cloth; and the matrix is one of epoxy resin, phenolic resin, and bismaleimide resin.
[0020] A wave-absorbing honeycomb composite material with a spatial gradient distribution of absorbent and a preparation method thereof are achieved by the following steps:
[0021] The first step is to prepare a semi-cured honeycomb core material;
[0022] The second step is to prepare the wave absorbing adhesive film layer;
[0023] The third step is to press the absorbing adhesive film layer into the cells of the semi-cured honeycomb core material according to the electrical performance design to obtain the absorbing honeycomb core material;
[0024] The fourth step is to heat-set the wave-absorbing honeycomb core material;
[0025] The fifth step is to bond the wave-absorbing honeycomb core material to the wave-transmitting skin to obtain a wave-absorbing honeycomb composite material.
[0026] Furthermore, the semi-cured honeycomb core material is aramid paper impregnated with phenolic resin, and the solvent is removed after drying; after long-term low-temperature treatment, the phenolic resin is in a semi-cured state, and the honeycomb core material has both a certain compressive resistance and thermal setting ability. The low-temperature treatment temperature is 70℃~90℃, and the treatment time is 6h-12h. During the low-temperature treatment process, it is also necessary to ensure that the phenolic resin on the honeycomb cell wall does not flow along the cell wall.
[0027] Furthermore, the wave absorbing adhesive film layer is composed of an absorbent and an adhesive. The absorbent has magnetic loss capability and is one or more of carbonyl iron powder, iron silicon aluminum, iron cobalt nickel, ferrite, etc. The adhesive is one of epoxy resin, phenolic resin, and bismaleimide resin.
[0028] Furthermore, the wave-absorbing adhesive film layer is prepared by calendaring or casting, and is in an uncured and flexible state, so that it is easy to be pressed into the honeycomb cells.
[0029] Furthermore, electrical performance design is carried out to determine the type of absorbent; electromagnetic simulation software is used to calculate and optimize the best gradient absorbing structure, determine the number of absorbing film layers in the absorbing honeycomb and the position of the absorbing film layers in the honeycomb cells; and then determine the thickness of each absorbing film layer and the content of the absorbent.
[0030] Furthermore, the absorbing film layer is pressed into the honeycomb cells using a two-step method. In the first step, the absorbing film is placed on a press and heated to 50°C to 80°C, and kept warm for 0.5h to 1h to soften the absorbing film; a semi-cured honeycomb core material is placed on top of the film, and a press is used to apply pressure to press the absorbing film into the honeycomb cells until the film completely enters the honeycomb cells. In the second step, a hard foam flat plate is placed under the honeycomb core material, and a press is used to continue to apply pressure to the honeycomb core material, and the honeycomb cell wall is cut and immersed in the hard foam, and the hard foam enters the honeycomb cells to push the absorbing film into the honeycomb cells; by controlling the stroke of the press, the position of the absorbing film in the honeycomb cells can be accurately controlled.
[0031] Furthermore, the fourth step is to heat-set the absorbing honeycomb core material, which is to place the semi-cured absorbing honeycomb on the mold surface (curved surface) and cure it by vacuum bag pressing or autoclave process. The curing temperature is 180℃~200℃ and the curing time is 2h~4h.
[0032] Furthermore, the wave-absorbing honeycomb core material is bonded to the wave-transmitting skin, and the skin is a wave-transmitting fiber cloth resin-based composite material. During bonding, the skin can be in a cured state or an uncured state. The skin and the wave-absorbing honeycomb core material are bonded using a plate-core adhesive.
[0033] The beneficial effects of the present invention compared with the prior art are as follows:
[0034] (1) The present invention pushes the absorbing adhesive film layer into the semi-cured honeycomb cells to form an impedance matching structure, thereby achieving precise control of the absorbing structure. The obtained absorbing honeycomb core material can be formed on a curved surface to meet the stealth requirements of curved surface components, thereby overcoming the problem that the absorbing honeycomb of the traditional impedance matching structure cannot change its thickness and cannot be processed to obtain a curved surface.
[0035] (2) The present invention pushes the absorbing film layer into different positions in the honeycomb cells by physical methods, thereby obtaining an impedance matching structure while keeping the honeycomb cells intact, thus overcoming the shortcomings of cross-linking of multi-layer absorbing honeycomb cell walls and insufficient compressive resistance.
[0036] (3) The present invention places the absorbing film into the honeycomb cells, and different types of absorbers can be added to meet different absorbing requirements; the absorber can be added in large quantities, and has excellent absorbing effect in an ultra-wide frequency range, thereby overcoming the shortcomings of the existing absorber-doped aramid paper absorbing honeycomb, such as limited absorber types (only fibrous) and low absorber content, and also overcomes the shortcomings of the thin absorbing layer thickness in the coated aramid paper absorbing honeycomb. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic structural diagram of the semi-cured wave-absorbing honeycomb core material that can be used for curved surface molding according to the present invention;
[0038] Figure 2 The present invention is a flow chart for preparing the wave-absorbing honeycomb composite material that can be used for curved surface molding;
[0039] Figure 3 It is a schematic diagram of the process of pushing the wave-absorbing adhesive film into the honeycomb cells of the present invention. DETAILED DESCRIPTION
[0040] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below through specific embodiments and drawings.
[0041] The present invention combines the characteristics of multi-layer absorbing honeycombs to propose an absorbing honeycomb composite material with an impedance matching structure and a spatial gradient distribution of absorbents and a preparation method. According to the electrical performance design, absorbing adhesive film layers with different electromagnetic properties are pushed into different positions in the cells of the semi-cured honeycomb core material, and the electromagnetic properties change gradiently along the cell direction to obtain an impedance matching structure. Figure 1 The wave-absorbing honeycomb is pasted on the surface (curved surface) of the product or mold and solidified to obtain the heat-set wave-absorbing honeycomb core material; the upper and lower surfaces are bonded to the wave-transmitting skin respectively to obtain a wave-absorbing honeycomb composite material with excellent performance to meet the stealth requirements of curved products.
[0042] According to the electrical performance design, the impedance matching structure of the absorbing film in the honeycomb core material is calculated and optimized to determine the type and content of the absorbent in the absorbing film layer, the thickness of the absorbing film layer, the number of absorbing film layers, and the position of the absorbing film layer in the honeycomb cell. Absorbents of different types and contents are mixed with adhesives, and the absorbing film layer is obtained by calendaring or casting. The calendaring or casting process in the present invention is a well-known technology in the art, and the specific process parameters are determined according to actual production needs.
[0043] The present invention also provides Figure 2 The microwave-absorbing honeycomb composite material and preparation method thereof which can be used for curved surface molding are shown, and are realized by the following steps:
[0044] 1. Preparation of semi-cured honeycomb core material
[0045] The semi-cured honeycomb core material in this step is aramid paper impregnated with phenolic resin, and the solvent is removed after drying; after long-term treatment at low temperature, the phenolic resin is in a semi-cured state, and the honeycomb core material has both certain compressive resistance and thermal setting ability.
[0046] Low temperature and long time treatment, the treatment temperature is 70℃~90℃, the treatment time is 6h-12h. During the low temperature treatment process, it is also necessary to ensure that the phenolic resin on the honeycomb pore wall does not flow along the pore wall.
[0047] 2. Preparation of Absorbent Film Layer
[0048] According to the electrical performance design, the impedance matching structure of the absorbing film in the honeycomb core material is calculated and optimized, and the type and content of the absorber in the absorbing film layer, the thickness of the absorbing film layer, the number of absorbing film layers, and the position of the absorbing film layer in the honeycomb cells are determined.
[0049] The wave absorbing film layer is composed of an absorbent and an adhesive. The absorbent has magnetic loss capability and is one or more of carbonyl iron powder, iron silicon aluminum, iron cobalt nickel, ferrite, etc. The adhesive is one of epoxy resin, phenolic resin, and bismaleimide resin.
[0050] According to the electrical performance design, different types and contents of absorbents are mixed with adhesives, and different absorbing film layers are obtained by casting or calendering process. The absorbent content in the absorbing film layer is 30wt% to 85wt%, and the thickness is 0.5mm to 3mm. The prepared absorbing film layers with different electromagnetic properties, A1, A2, A3, A4...An, the absorbent content and electromagnetic parameters gradually increase.
[0051] 3. Based on the electrical performance design, the semi-cured honeycomb core material cells are built with an absorbing film layer
[0052] The absorbing film is pressed into the honeycomb cells using a two-step method, such as Figure 3As shown. The first step is to place the absorbing film on a press and heat it to 50℃~80℃, keep it warm for 0.5h~1h, and soften the absorbing film; place a semi-cured honeycomb core material on top of the film, use a press to pressurize it, and press the absorbing film into the honeycomb cells until the film completely enters the honeycomb cells. The second step is to place a hard foam flat plate under the honeycomb core material, use a press to continue to pressurize the honeycomb core material, cut the honeycomb pore wall and immerse it in the hard foam, the hard foam enters the honeycomb cells, and push the absorbing film into the honeycomb cells; by controlling the stroke of the press, the position of the absorbing film in the honeycomb cells can be accurately controlled.
[0053] According to the designed order and position, push the absorbing film layer into the semi-cured honeycomb core material cells one by one. Figure 3 As shown in the second step. Place the absorbing film layer A1 at the bottom of the honeycomb core material grid, place a hard foam flat plate under the absorbing film layer, and push the film layer from bottom to top to the set position after pressurization. Place A2, A3...An film layers in sequence and push them to the corresponding positions respectively to obtain a semi-cured absorbing honeycomb core material with an impedance matching structure.
[0054] 4. Heat setting of microwave-absorbing honeycomb core
[0055] In this step, the wave-absorbing honeycomb core material is heat-set by placing the semi-cured wave-absorbing honeycomb on the mold surface (curved surface), with the lower surface of the honeycomb core material being the mold-attaching surface. The vacuum bag pressing or autoclave process is used for curing, with a curing temperature of 180°C to 200°C and a curing time of 2h to 4h.
[0056] During the heat setting process, the absorbing film layer will also heat up and solidify. It softens during the heating process. Due to the high proportion of magnetic absorber, the absorbing film will not flow along the honeycomb pore wall, maintaining the impedance matching structure. The resin on the absorbing film layer and the honeycomb core pore wall is not fully cured. The resin has better wettability during the heating and insulation process, and after complete curing, it ensures good bonding strength between the two.
[0057] After the microwave-absorbing honeycomb core material is cured, the shape of the designed curved surface is maintained, thereby obtaining a heat-set microwave-absorbing honeycomb core material.
[0058] 5. The wave-absorbing honeycomb core material is bonded to the wave-transmitting skin to obtain a wave-absorbing honeycomb composite material
[0059] The wave-transmitting skin in this step is a wave-transmitting fiber cloth resin-based composite material, the wave-transmitting fiber cloth can be quartz fiber cloth or glass fiber cloth, and the resin can be epoxy resin, phenolic resin, cyanate resin or bismaleimide resin.
[0060] The wave-transmitting fiber / resin prepreg can be directly laid on the upper and lower surfaces of the wave-absorbing honeycomb core material and placed on a curved mold for curing; or the skin prepreg can be first laid on the curved mold, and the upper and lower skins can be cured separately, and then the upper and lower skins can be laid and bonded to the upper and lower surfaces of the wave-absorbing honeycomb core material.
[0061] The skin and the absorbing honeycomb core material are bonded with plate-core adhesive, and the bonding process is autoclave or vacuum bag process, and the absorbing honeycomb composite material is obtained by laying on the curved mold for bonding and curing. The curing temperature is 175℃~185℃, and the curing time is 2h~4h.
[0062] The present invention is described in detail below with reference to the accompanying drawings and specific examples.
[0063] Example 1
[0064] Step 1. According to actual needs, the total thickness of the absorbing honeycomb composite material is determined to be 27 mm, of which the thickness of the absorbing honeycomb core material is 25 mm, the shape of the honeycomb cell is hexagonal, the length is 2.77 mm, and the upper and lower skins are both 1 mm thick quartz fiber cloth / epoxy resin composite materials.
[0065] Semi-cured absorbing honeycomb core material is prepared by impregnating phenolic resin with aramid paper, and the preparation process is as follows: gluing aramid paper to core strips, laminating, hot pressing, stretching, dipping, drying, and then low-temperature treatment, and keeping warm at 80°C for 8h; after low-temperature treatment, a semi-cured honeycomb core material is obtained, and the phenolic resin on the honeycomb pore wall is in a semi-cured state and has heat setting ability.
[0066] Step 2. Design the electrical performance of the absorbing honeycomb according to the absorbing requirements in the 1GHz-18GHz frequency band. Use electromagnetic simulation software to calculate the optimal impedance matching absorbing structure. The absorber in the absorbing film layer is carbonyl iron powder, the adhesive is epoxy resin, the film layer thickness is 2.0mm, and there are six layers in total, namely A1, A2, A3, A4, A5, and A6. The mass ratios of the absorbers in the absorbing film layers A1, A2, A3, A4, A5, and A6 are 30%, 40%, 50%, 60%, 70%, and 85%, respectively. The positions of each absorbing layer, i.e., the distance from the lower surface, are 22mm, 18mm, 14mm, 10mm, 6mm, and 1mm, respectively. From the upper surface to the lower surface of the honeycomb core material (along the honeycomb thickness direction), the absorbing films in the honeycomb cells are A1, A2, A3, A4, A5, and A6, respectively.
[0067] According to the designed absorbent content, carbonyl iron powder with different contents was evenly mixed with epoxy resin, and absorbing films with a thickness of 2.0 mm were prepared by calendering. The obtained absorbing films were A1, A2, A3, A4, A5, and A6 respectively.
[0068] Step 3: Press the absorbing film into the honeycomb cells. The first step is to place the absorbing film on a press and heat it to 60°C. Keep it warm for 0.5 hours to soften the absorbing film. Place a semi-cured honeycomb core material on top of the film and use a press to apply pressure to press the absorbing film into the honeycomb cells until the film is completely inside the honeycomb cells. The second step is to place a hard foam flat plate under the honeycomb core material and continue to pressurize the honeycomb core material using a press. Cut the honeycomb cell wall and immerse it in the hard foam. The hard foam enters the honeycomb cells and pushes the absorbing film into the honeycomb cells. By controlling the stroke of the press, the position of the absorbing film in the honeycomb cells can be precisely controlled.
[0069] First, the absorbing film A1 is pushed in from the bottom of the honeycomb core material, and the absorbing film A1 is pushed into the cells using hard foam, and the insertion depth is controlled to be 22mm to ensure the accurate position of the A1 layer in the honeycomb. The A2, A3, A4, A5, and A6 layers are placed in the cells in turn, and the film is pushed into the designed position using metal columns, with the insertion depths of 18mm, 14mm, 10mm, 6mm, and 1mm respectively. A semi-cured absorbing honeycomb core material with impedance matching is obtained, in which the A1 and A6 absorbing film layers are 1mm away from the upper and lower surfaces of the honeycomb core material, in order to increase the bonding strength between the honeycomb core material and the skin of the plate-core adhesive bonding.
[0070] Step 4. Design a curved mold for honeycomb curing according to the actual surface of the product. Place the semi-cured absorbing honeycomb core material on the mold surface (curved surface), with the lower surface of the honeycomb core material as the mold surface. Use vacuum bag pressing process for curing, the curing temperature is 180℃, and the curing time is 2h. After curing, remove it to obtain the heat-set absorbing honeycomb core material, and mark the upper and lower surfaces.
[0071] Step 5: Use quartz fiber cloth / epoxy resin as the skin material, and the thickness of the upper and lower skins is 1.0 mm. Lay the quartz fiber cloth / epoxy resin prepreg on the mold surface with a thickness of 1.0 mm, and cure it by vacuum bag pressing process at a curing temperature of 130°C and a curing time of 2 hours to obtain the upper skin. Use the same method to prepare the lower skin.
[0072] The lower skin, plate-core adhesive, absorbing honeycomb core material, plate-core adhesive and upper skin were laid on the mold surface in this order and cured by vacuum bag pressing process at a curing temperature of 180°C and a curing time of 3h to obtain an absorbing honeycomb composite material.
[0073] The absorbing honeycomb composite material has a smooth appearance, and the bonding quality between the skin and the honeycomb core material is good; the profile is consistent with the theoretical curved surface, and the deviation is less than 0.2mm. The curved absorbing honeycomb composite material cannot be tested for its absorbing performance (reflectivity). Using the same process, the absorbing honeycomb core material is cured on a flat mold, and then the absorbing honeycomb composite material (equivalent flat plate) is prepared. Its absorbing performance is 1GHz~2GHz reflectivity ≤-20dB, 2GHz~8GHz reflectivity ≤-25dB, and 8GHz~18GHz reflectivity ≤-30dB. The absorbing honeycomb has excellent absorbing effect in the required electromagnetic wave frequency band (1GHz-18GHz).
[0074] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0075] Example 2
[0076] The absorbing frequency of the absorbing honeycomb composite material is mainly 0.5GHz-8GHz, the absorber is sendustine flaky powder, the mass ratios are 1%, 2%, 6%, 12%, 24% and 30% respectively, and the rest are the same as in Example 1, to obtain a absorbing honeycomb composite material.
[0077] The absorbing honeycomb composite material has a smooth appearance, good bonding quality between the skin and the honeycomb core material; the profile is consistent with the theoretical curved surface, with a deviation of less than 0.2mm. The absorbing performance of the absorbing honeycomb composite material (equivalent flat plate) is 0.5GHz~1GHz reflectivity ≤-10dB, 1GHz~2GHz reflectivity ≤-20dB, 2GHz~8GHz reflectivity ≤-25dB, 8GHz~18GHz reflectivity ≤-20dB. The absorbing honeycomb has excellent absorbing effect in the required electromagnetic wave frequency band (0.5GHz-8GHz).
[0078] Example 3
[0079] The absorbing frequency of the absorbing honeycomb composite material is mainly 0.5GHz-18GHz, and the thickness is 32mm, of which the absorbing honeycomb core material is 30mm thick, and the upper and lower skins are both 1mm thick. The absorbent is carbonyl iron powder and iron silicon aluminum, each accounting for 50%, and the absorbing film layer is divided into 7 layers; each layer is 1.5mm thick, and the absorbent content mass ratio is 30%, 35%, 45%, 55%, 65%, 75%, 85% respectively, and the position, i.e., the distance from the lower surface, is 27mm, 24mm, 20mm, 15mm, 10mm, 5mm, and 1mm respectively. The rest is the same as in Example 1, and an absorbing honeycomb composite material is obtained.
[0080] The absorbing honeycomb composite material has a smooth appearance, good bonding quality between the skin and the honeycomb core material; the profile is consistent with the theoretical curved surface, with a deviation of less than 0.2mm. The absorbing performance of the absorbing honeycomb composite material (equivalent flat plate) is 0.5GHz~1GHz reflectivity ≤-8dB, 1GHz~2GHz reflectivity ≤-18dB, 2GHz~8GHz reflectivity ≤-25dB, 8GHz~18GHz reflectivity ≤-28dB. The absorbing honeycomb has excellent absorbing effect in the required electromagnetic wave frequency band (0.5GHz-18GHz).
[0081] Other implementations:
[0082] Other implementations mainly involve changing the thickness of the honeycomb core material, the type and content of the absorber, the thickness, number of layers and position of the absorbing film layer, which are essentially the same as the above three implementations, and the preparation method remains unchanged.
[0083] Comparative Example 1: The absorbent content in the absorbing film layer is 50%, and the rest is the same as Example 1, to obtain an absorbing honeycomb composite material. The absorbing honeycomb composite material has a smooth and good appearance, and the bonding quality between the skin and the honeycomb core is good; the profile is consistent with the theoretical curved surface, and the deviation is less than 0.2mm. The absorbing performance of the absorbing honeycomb composite material (equivalent flat plate) is 1GHz~2GHz reflectivity ≤-10dB, 2GHz~8GHz reflectivity ≤-15dB, 8GHz~18GHz reflectivity ≤-20dB. The absorbing performance of the absorbing honeycomb in the required electromagnetic wave frequency band (1GHz-18GHz) is poor.
[0084] Comparative Example 2: The honeycomb core material substrate is a cured honeycomb core material, and the rest is the same as Example 1, to obtain an absorbing honeycomb composite material. The absorbing honeycomb composite material cannot be heat-set, has a poor appearance, cracks in the honeycomb core material, and the bonding quality between the skin and the honeycomb core material is poor; the profile is very different from the theoretical curved surface, with a deviation of more than 5mm. The absorbing performance of the absorbing honeycomb composite material (equivalent flat plate) is 1GHz~2GHz reflectivity ≤-18dB, 2GHz~8GHz reflectivity ≤-23dB, and 8GHz~18GHz reflectivity ≤-28dB. The absorbing honeycomb has a good absorbing effect in the required electromagnetic wave frequency band (1GHz-18GHz). This is the absorbing performance tested under a flat plate. The absorbing honeycomb composite material of Comparative Example 2 cannot be heat-set and bent, will crack, and cannot be used on curved surfaces.
[0085] The specific embodiments and drawings of the present invention disclosed above are intended to help understand the content of the present invention and implement it accordingly. It can be understood by those skilled in the art that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention. The present invention should not be limited to the contents disclosed in the embodiments and drawings of this specification, and the scope of protection of the present invention shall be subject to the scope defined in the claims.
Claims
1. A microwave-absorbing honeycomb composite material with a spatial gradient distribution of absorbent, characterized in that: It includes an upper skin, a lower skin, a honeycomb core material and an absorbing film layer; the honeycomb core material is formed by curing a semi-cured honeycomb core material; the absorbing film layer is located in the pores of the honeycomb core material, and the honeycomb core material containing the absorbing film layer is located between the upper skin and the lower skin; the absorbing film layer contains an absorbent, and the electromagnetic properties of the absorbent in each absorbing film layer are distributed in a gradient.
2. The wave-absorbing honeycomb composite material according to claim 1, characterized in that: The absorbing honeycomb composite material is prepared by the following steps: according to the electrical performance design, absorbing adhesive film layers with different electromagnetic properties are pressed into different positions in the cells of the semi-cured honeycomb core material, and the electromagnetic properties change gradually along the cell direction to obtain an impedance matching structure; the semi-cured honeycomb core material including the absorbing adhesive film layer is attached to the surface of the mold for curing to obtain the heat-set absorbing honeycomb core material; the upper and lower surfaces of the absorbing honeycomb core material are respectively bonded to the upper skin and the lower skin.
3. The wave-absorbing honeycomb composite material according to claim 1, characterized in that: The semi-cured honeycomb core material is aramid paper impregnated with phenolic resin, which is dried to remove the solvent and then subjected to low-temperature and long-term treatment to adjust the phenolic resin to a semi-cured state; the low-temperature and long-term treatment has a treatment temperature of 70°C to 90°C and a treatment time of 6h-12h. During the low-temperature treatment, it is ensured that the phenolic resin on the honeycomb pore wall does not flow along the pore wall.
4. The wave-absorbing honeycomb composite material according to claim 1, characterized in that: The absorbing film layer includes an absorbent and an adhesive, and the thickness of the absorbing film layer is 0.5mm to 3mm; the absorbent has electromagnetic loss capability and is at least one of carbonyl iron powder, iron silicon aluminum, iron cobalt nickel, and ferrite, with a content of 30wt% to 85wt%; the adhesive is one of epoxy resin, phenolic resin, and bismaleimide resin.
5. The wave-absorbing honeycomb composite material according to claim 1, characterized in that: The type of absorbent is determined by conducting electrical performance design. The best gradient absorbing structure is calculated and optimized using electromagnetic simulation software to determine the number of absorbing film layers in the absorbing honeycomb, the position of the absorbing film layers in the honeycomb cells, the thickness of each absorbing film layer and the content of the absorbent.
6. The wave-absorbing honeycomb composite material according to claim 1, characterized in that: The upper skin and the lower skin are wave-transmitting resin-based composite materials, including a reinforcement layer and a matrix, wherein the reinforcement is one of quartz fiber cloth and glass fiber cloth, and the matrix is one of epoxy resin, phenolic resin, and bismaleimide resin.
7. A method for preparing a wave-absorbing honeycomb composite material with a spatial gradient distribution of absorbent, characterized in that: The following steps are involved: preparing a semi-cured honeycomb core material; preparing a wave absorbing adhesive film layer; According to the electrical performance design, the microwave absorbing adhesive film layer is pressed into the cells of the semi-cured honeycomb core material to obtain the microwave absorbing honeycomb core material; Heat setting the wave-absorbing honeycomb core material; The wave-absorbing honeycomb core material is bonded to the upper skin and the lower skin to obtain a wave-absorbing honeycomb composite material.
8. The preparation method according to claim 7, characterized in that: The wave-absorbing adhesive film layer is prepared by calendaring or casting, and is in an uncured and flexible state, so it is easy to be pressed into the honeycomb cells.
9. The preparation method according to claim 7, characterized in that: The absorbing film layer is pressed into the honeycomb cells in two steps: In the first step, the absorbing film is placed on a press and heated to 50°C to 80°C, and kept warm for 0.5h to 1h to soften the absorbing film, and a semi-cured honeycomb core material is placed on the film; the press is used to press the absorbing film into the honeycomb cells until the film is completely inside the honeycomb cells; The second step is to place a hard foam flat plate under the honeycomb core material, use a press to continue to pressurize the honeycomb core material, cut the honeycomb pore wall and immerse it in the hard foam, the hard foam enters the honeycomb pores, and push the absorbing film into the honeycomb pores; the position of the absorbing film in the honeycomb pores is precisely controlled by controlling the stroke of the press.
10. The preparation method according to claim 7, characterized in that: The heat setting of the wave-absorbing honeycomb core material is to place the wave-absorbing honeycomb in a semi-cured state on the mold surface and cure it by vacuum bag pressing or autoclave process, the curing temperature is 180°C to 200°C, and the curing time is 2h to 4h; the wave-absorbing honeycomb core material is bonded to the upper skin and the lower skin, wherein the skin is a wave-transmitting fiber cloth resin-based composite material, the skin is in a cured state or an uncured state during bonding, and the skin and the wave-absorbing honeycomb core material are bonded by plate-core adhesive.
Citation Information
Patent Citations
Wave-absorbing glue film, preparation method thereof and impedance-gradual-change wave-absorbing structural component
CN109423008A
Wave-absorbing honeycomb with impedance matching structure and preparation method thereof
CN115891293A
Forming method of large-core lattice curvature honeycomb sandwich composite material workpiece
CN116945648A
Cited By
Wave-absorbing honeycomb with patterns and preparation method thereof
CN121355611A
Broadband wave-absorbing honeycomb sandwich foam based on microsphere carrier and preparation method of broadband wave-absorbing honeycomb sandwich foam
CN122232256A
A microsphere carrier-based broadband wave-absorbing honeycomb sandwich foam and a preparation method thereof
CN122232256B